Zimbabwe : 2005 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Zimbabwe. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Zimbabwe's pace of economic deterioration slowed somewhat in 2004, but appears to have picked up again in the first half of 2005. IMF staff estimates that real GDP fell by about 4 percent in 2004, compared with a contraction of 10 1\2 percent the preceding year. Monetary policy has been tightened, but not consistently. Overnight interest rates were raised sharply in early 2004 and lowered subsequently as inflation declined, with real interest rates maintained at high levels for most of the year.